Influência do consumo alimentar e do padrão de atividade física sobre o estado nutricional de adolescentes de Piedade, São Paulo - Enes, Carla Cristina; Pegolo, Giovana Eliza [UNESP]; Silva, Marina Vieira Da (Sociedade de Pediatria de São Paulo, 2009)
OBJECTIVE: To identify dietary and physical activity factors associated to the nutritional status of adolescent students. METHODS: Cross-sectional study of 105 adolescents of both genders, aged 10 to 14 years, studying at public schools in Piedade, São Paulo, Brazil. Data regarding food intake (24 hour recall), physical activity patterns (physical and sedentary activities) and nutritional status measured by body mass index were collected. The adolescents were characterized as insufficiently active if physical activities were practiced for less than 300 minutes per week. They were considered sedentary if they spent two hours or more per day in passive activities. Multiple linear regression was performed to identify factors associated to the nutritional status. RESULTS: The prevalence of overweight was higher among boys (17.9 versus 13.6%, p<0.05) and 18.0% of the adolescents were considered insufficiently active. There was no association between dietary and nutritional status variables. A significant difference was observed only for the time spent playing videogames (p=0.005), that was higher among eutrophic adolescents. Seven in ten adolescents spent more than two hours a day on sedentary activities (watching television, using the computer and playing videogames). In multiple regression analysis, only age was positively associated with the BMI (p=0.001). CONCLUSIONS: Further prospective investigations are necessary to establish clearer relationships among factors related to lifestyle and body mass index among adolescents.

OBJETIVO: Identificar os fatores dietéticos e de atividade física associados ao estado nutricional de adolescentes escolares. MÉTODOS: Estudo transversal com 105 adolescentes de ambos os sexos, idade de 10 a 14 anos, matriculados em escolas públicas de Piedade (SP). Foram coletadas informações sobre consumo alimentar (recordatório 24 horas), padrão de atividade física (atividades físicas e sedentárias) e estado nutricional avaliado pelo índice de massa corporal. Consideraram-se insuficientemente ativos os adolescentes que praticavam menos de 300 minutos/semana de atividade física. Foram classificados como sedentários aqueles que dedicavam período de tempo igual ou superior a duas horas por dia a atividades passivas. Para identificar os fatores associados ao estado nutricional, recorreu-se à regressão linear múltipla. RESULTADOS: A prevalência de excesso de peso foi maior entre os meninos (17,9 versus 13,6%, p<0,05). Dos adolescentes, 18% foram considerados insuficientemente ativos. Não houve associação entre as variáveis dietéticas e o estado nutricional. Observou-se diferença significativa apenas para o tempo dedicado para jogar videogame (p=0,005), que foi maior nos adolescentes eutróficos. Sete em cada dez adolescentes dedicavam mais de duas horas diárias às atividades sedentárias, como assistir à televisão, usar o computador e jogar videogame. Na análise múltipla, somente a idade se associou positivamente ao IMC (p=0,001). CONCLUSÕES: Há necessidade de novas investigações de caráter prospectivo que estabeleçam relações mais claras entre os fatores relacionados ao estilo de vida e o índice de massa corporal em adolescentes.
Influence of food intake and physical activity patterns on the nutritional status of adolescents from Piedade, São Paulo, Brazil
Keywords: adolescent; motor activity; food consumption; nutritional status; adolescente; atividade física; consumo de alimentos; estado nutricional